Separation, Antioxidant and Antimicrobial Activities of Chemical Constituents from Exocarp of Juglans mandshurica Maxim - Shi, Ai-Hua; Huang, Jia-Wei; Liu, Yuan-Hui; Yuan, Ke (Asian Journal of Chemistry, 2013)
This paper reports, the studies of the chemical constituents and antioxidant and antimicrobial activities from exocarp of Juglans mandshurica Maxim. The compounds were isolated by Diaion HP-20, Sephadex LH-20 and MCI CHP-20 column chromatography methods, their structures were identified by physicochemical properties and spectroscopic analysis. Twelve compounds were elucidated as 5-hydroxy-7-methoxy sylflavanone (1), chrysophanol (2), juglone (3), 4-hydroxy-cinnamic acid methylester (4), 5,7-dihydroxy-sylflavanone (5), vanillin (6), kaempferol (7), vanillic acid (8), chlorogenic acid (9), cinnamic acid (10), 4-hydroxy-3-methoxy benzyl-b-D-glucoside (11), 4-hydroxy-cinnamic acid ethylester (12). Meanwhile, the effect of scavenging free radicals of twelve compounds were assayed by using the DPPH· method with Trolox as control to evaluate their antioxidant capacities. Gram-positive (Staphyloccocus aureus) and gram-negative (Escherichia coli) were selected as the indicator microorganisms to evaluate the antimicrobial activity. Antimicrobial properties were estimated by the agar diffusion method. All of the compounds possessed certain antioxidant and antimicrobial activities.